Application value of high-quality nursing combined with methylprednisolone in treatment of sudden deafness: methylprednisolone in treatment of deafness - Lv, Haixia; Zhang, Yufang (Progress in Nutrition, 2021)
Objective: Explore the application value of high-quality nursing combined with methylprednisolone in the treatment of sudden deafness. Methods: The patients who came to our hospital for treatment due to sudden deafness from January 2017 to December 2019 were selected as the research object, and were divided into a control group (n=65) and an observation group (n=65) according to the random number table method. The group used routine nursing intervention, and the observation group used high-quality nursing intervention combined with methylprednisolone intervention to compare the efficacy, negative emotions, quality of life, nursing satisfaction and PTA of the two groups. Results: The effective rate of the observation group was 90.77% higher than that of the control group of 76.92%, the difference was statistically significant (P <0.05); the SAS and SDS scores of the two groups before intervention were compared, and there was no statistically significant difference (P>0.05), The SAS and SDS scores of both groups decreased, and the observation group was significantly lower than the control group, the difference was statistically significant (P <0.05); the quality of life score of the observation group after intervention was higher than the control group, the difference was statistically significant (P <0.05); the nursing satisfaction of the observation group was 90.77% significantly higher than that of the control group 73.85%, the difference was statistically significant (P <0.05); the PTA of both groups decreased after intervention, and the PTA of the observation group was lower than that of the control group , The difference was statistically significant (P<0.001).Conclusion: High-quality nursing combined with methylprednisolone has a significant effect on sudden deafness, which can relieve patients’ negative emotions, improve quality of life and nursing satisfaction, and is worthy of promotion.